2009
DOI: 10.1369/jhc.2009.953497
|View full text |Cite
|
Sign up to set email alerts
|

Protein Extraction of Formalin-fixed, Paraffin-embedded Tissue Enables Robust Proteomic Profiles by Mass Spectrometry

Abstract: Global mass spectrometry (MS) profiling and spectral count quantitation are used to identify unique or differentially expressed proteins and can help identify potential biomarkers. MS has rarely been conducted in retrospective studies, because historically, available samples for protein analyses were limited to formalin-fixed, paraffin-embedded (FFPE) archived tissue specimens. Reliable methods for obtaining proteomic profiles from FFPE samples are needed. Proteomic analysis of these samples has been confounde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
81
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 41 publications
7
81
0
Order By: Relevance
“…Proteins from sample paraffin tissue blocks were extracted using the protocols established previously (17)(18). The protein concentration was measured by D c protein assay (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Proteins from sample paraffin tissue blocks were extracted using the protocols established previously (17)(18). The protein concentration was measured by D c protein assay (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…The extracted RNA from formalin-fixed paraffin-embedded tissue is used for quantitative real-time reverse-transcriptase polymerase chain reaction (qRT-PCR) (Castiglione et al 2007), DNA array technologies (Lehmann and Kreipe 2001), and mRNA copy number analysis (von Smolinski et al 2005). Protein expression in formalin-fixed paraffin-embedded tissue has been analyzed by immunohistochemistry, western blot analysis and mass spectrometry (Crockett et al 2005;Ostasiewicz et al 2010;Scicchitano et al 2009). Gene and protein expression profiles of formalin-fixed paraffin-embedded tissue can provide insights into molecular mechanisms of diseases, but there are difficulties because of the marked degradation and cross-linking of biomolecules by fixation.…”
mentioning
confidence: 99%
“…However, the polymers in OCT medium (i.e., PVA and PEG) interfere with MS analysis by suppressing ion formation [7], and thus need to be removed from samples. A few proteomic studies have been conducted in OCTembedded tissues [8][9][10][11][12]. In some studies, OCT was cleared in subsequent experimental steps (e.g., any separation approach that involved running polyacrylamide gels) [8,9,12].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, OCT was cleared in subsequent experimental steps (e.g., any separation approach that involved running polyacrylamide gels) [8,9,12]. While in other studies, the number of proteins identified was compromised due to incomplete elimination of OCT medium [10,11]. One challenge associated with fresh frozen tissues is that sample size/amount may be limiting and finite.…”
Section: Introductionmentioning
confidence: 99%